The co-conditioning of dis/ability and gender: An intersectionality study of Powerchair Hockey - Paccaud, Laurent (Frontiers in Sports and Active Living, 2022)
This paper aims at initiating scholars to consider dis/ability as a category of analysis when doing intersectionality in sociology of sport. First, it introduces a conceptual framework that allows researchers to engage with the issue of the body and its physical and cognitive functions, as well as to address how the ability–disability system intersects with various other salient systems of oppression and privilege. I call this concept the intersectional co-conditioning of dis/ability, whereby experiences of dis/ability are fundamentally conditioned by (and also condition in return) other systems of difference and inequality. The framework provides scholars with theoretical tools that will help them to investigate body-related issues while avoiding the pitfall of essentializing dis/abilities. Second, this work offers an application of the abovementioned conceptual framework, focusing on the co-conditioning of dis/ability and gender. Based on a multi-sited ethnography of Powerchair Hockey in Switzerland, I investigate different aspects of this sport practiced by people living with so-called "severe" physical dis/abilities. The results highlight the tensions, contradictions and paradoxes that both male and female players face as they (re)negotiate their positions within the matrix of domination. This application demonstrates the explanatory power of considering the intersectional co-conditioning of dis/ability.